The strong "zero-two" law for positive contractions of banach-kantorovich Lp-lattices - Ganiev, Inomjon; Mukhamedov, Farrukh; Bekbaev, Ural (The Scientific and Technological Research Council of Turkey, 2015)
In the present paper we study dominated operators acting on Banach{Kantorovich Lp -lattices, constructed by a measure m with values in the ring of all measurable functions. Using methods of measurable bundles of Banach{ Kantorovich lattices, we prove the strong \zero-two" law for positive contractions of Banach{Kantorovich Lp -lattices.